Library staffing in the 4th Industrial Revolution: Skill-gap Analysis of library professionals - Osahon Igbinovia, Magnus; Bayor Odelami, Joseph; Gana Malgwi, Philip (Ghana Library Journal, 2025)
The skill-gap precipitated by the inadequacy of Library and Information Science (LIS) curricula to meet the skill requirements of employers in the Fourth Industrial Revolution (4IR) remains under-researched. Consequently, this study was carried out to ascertain the skill-gap between employers’ skill requirements and skill coverage in library schools’ curricula. To achieve this, the authors carried out content analysis of two major job websites (ALA JobLIST and Indeed) and four (4) library schools’ curricula from 4 different countries, two (2) each from the Global North and Global South. The skill coverage was measured using 3-point likert scale with a criterion mean of 2.0, against which the average rating score (calculated mean) was considered. The study found that employers demanded more of soft skills, followed by leadership/ managerial skills, and then technical/ technological skills. The library schools’ curricula analyzed revealed that soft skills and leadership/managerial skills were not adequately covered. However, technical/technological skills were adequately covered in the curricula. The study revealed a skill-gap with respect to soft skills and leadership/managerial skills. It concluded that library schools should train students in the light of current realities, periodically reviewing their curricula to cater for the changing skills requirement of employers in order to produce graduates that are employable, with high market value. The study contributes in providing a justification for revamping library schools’ curricula in light of the changes in the skill expectations that characterizes the 4IR. The value of this study is reinforced by the current fluidity in the employment landscape of LIS profession.